PROGRAM PENDAMPINGAN KELOMPOK MASYARAKAT DALAM PRODUKSI MASKER DAN ANTISEPTIK SERTA PENYEMPROTAN DISINFEKTAN DI DESA KWARON : COMMUNITY GROUP ASSISTANCE PROGRAM IN THE PRODUCTION OF MASK , ANTISEPTIC AND DISINFECTANT SPRAYING IN KWARON VILLAGE - Meriana Wahyu Nugroho; Niken Grah Prihartanti (Jurnal Pengabdian Masyarakat Kesehatan, 2021)
As one of the efforts to support and strengthen the Covid-19 prevention and control program carried out by the Government and increase the awareness of the Academic Community in preventing the spread and handling of COVID-19, it is necessary to have a community service activity that involves the role of the community. This is not only aimed at preventing the spread of Covid-19, but also to provide a stimulus for the economy of the people who are increasingly sluggish due to the pandemic. Currently, it is not only health whose condition is in the spotlight, but the community's economy is also declining so it is in dire need of activities that can help provide income. Some community service activities that can reactivate Several community service programs that can be provided for communities affected by COVID-19 include: a). mask making program; b) program for making masks; and c). disinfectant spraying program in the mosque. This activity can help the economy of the Kwaron Village community and also help implement activities that support health protocols during the pandemic.